SEJAUHMANA BUDAYA ORGANISASI MEMPENGARUHI KINERJA ORGANISASI? BUKTI DARI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL, KABUPATEN TRENGGALEK, PROVINSI JAWA TIMUR - Adfin Rochmad Baidhowah (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Cultural aspects within an organization will determine the direction of the performance of an organization whether leading to a better pendulum or toward a stagnant pendulum. The issue of the performance of e-ID card service in the Department of Population and Civil Registry of Trenggalek Regency shows the absence of aspect in organizational culture which has an impact on the organization's performance whether it is evaluated objectively internal government and objectively from the viewpoint of the service recipient community. Organizational culture is a system of shared meanings embraced by members who distinguish an organization from other organizations. This shared system of meanings, when examined more thoroughly, is a set of key characteristics valued by an organization. Research on the influence of organizational culture on organizational performance in the Department of Population and Civil Registry of Trenggalek Regency using quantitative method with survey research approach conducted on the object of research. The influence of organizational culture variable (X) toward organizational performance (Y) shows the total influence of p = 0,584 or 58,4% and t value equal to 2,099 and t value table equal to 1,985, giving meaning that there is significant influence of organizational culture variable as Independent variable toward performance variable. And the value of the effect of epsilon variables ie other variables not studied in this study, that is equal to 0.416 or 41.6%. Key Words: Organizational Culture, Organizational Performance and eKTP Service.